Charge transfer doping of graphene without degrading carrier mobility - Yuzheng Guo (Journal of Applied Physics, 2017)
Density functional calculations are used to analyze the charge transfer doping mechanism by molecules absorbed onto graphene. Typical dopants studied are AuCl3, FeCl3, SbF5, HNO3, MoO3, Cs2O, O2, and OH. The Fermi level shifts are correlated with the electron affinity or ionization potential of the dopants. We pay particular attention to whether the dopants form direct chemisorptive bonds which cause the underlying carbon atoms to pucker to form sp3 sites as these interrupt the π bonding of the basal plane, and cause carrier scattering and thus degrade the carrier mobility. Most species even those with high or low electronegativity do not cause puckering. In contrast, reactive radicals like -OH cause puckering of the basal plane, creating sp3 sites which degrade mobility.